2015
DOI: 10.1186/s12885-015-1802-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of activated Gαq to the tumor suppressor Fhit is enhanced by phospholipase Cβ

Abstract: BackgroundG proteins are known to modulate various growth signals and are implicated in the regulation of tumorigenesis. The tumor suppressor Fhit is a newly identified interaction partner of Gq proteins that typically stimulate the phospholipase C pathway. Activated Gαq subunits have been shown to interact directly with Fhit, up-regulate Fhit expression and enhance its suppressive effect on cell growth and migration. Other signaling molecules may be involved in modulating Gαq/Fhit interaction.MethodsTo test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Both these pathways are tightly related to cancer progression and apoptosis. In particular, it has been demonstrated that G protein-coupled receptors are involved in BC progression and that Gq signaling promotes cancer cell apoptosis through phospholipase C [ 77 79 ]. On the other hand, protein kinase A signaling has been shown to promote mammary tumorigenesis [ 80 ] and to determine ERα repositioning at promoters and tamoxifen resistance [ 81 ]; its inhibition by ERβ–AGO2 cooperation may thus negatively affect cancer cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Both these pathways are tightly related to cancer progression and apoptosis. In particular, it has been demonstrated that G protein-coupled receptors are involved in BC progression and that Gq signaling promotes cancer cell apoptosis through phospholipase C [ 77 79 ]. On the other hand, protein kinase A signaling has been shown to promote mammary tumorigenesis [ 80 ] and to determine ERα repositioning at promoters and tamoxifen resistance [ 81 ]; its inhibition by ERβ–AGO2 cooperation may thus negatively affect cancer cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%